Eucalypts as a biofuel feedstock. Issue 6 (November 2011) - Shepherd, Mervyn; Bartle, John; Lee, David J; Brawner, Jeremy; Bush, David; Turnbull, Paul; Macdonel, Paul; Brown, Troy R; Simmons, Blake; Henry, Robert
Eucalypts are both a proven but largely unexplored source of woody biomass for biofuel production. Few of the some 900 species have been evaluated for cropping, yet among them are the most productive and versatile biomass species in the world, grown in over 90 countries, with species found to suit most tropical and temperate climates. The biology, science and technology underlying the breeding and growing of eucalypts and their potential for biofuel production are reviewed. How eucalypts meet sustainability and economic criteria for biofuel feedstocks, and the advantages of woody feedstocks broadly, are considered. Relevant aspects of eucalypt taxonomy, evolution, natural distribution, human dispersal, composition, domestication and biotechnology of the groups'' potential as a biofuel feedstock resource are reviewed. Two case studies are outlined, illustrating species identification, domestication and harvesting processes where eucalypts are prospective biofuel feedstocks. Eucalypts are strong contenders as a universal woody biomass feedstock for biofuel.